1994
DOI: 10.1161/01.atv.14.7.1066
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantitation of calcific atherosclerosis by ultrafast computed tomography in children and young adults with homozygous familial hypercholesterolemia.

Abstract: Ultrafast computed tomography (CT) is a new method for detecting calcific lesions in the coronary arteries. The ability of CT to detect and quantify coronary artery atherosclerosis in children and young adults at risk for malignant atherogenesis was evaluated. A total of 11 consecutive familial hypercholesterolemic (FH) homozygotes (3 to 37 years old) participated. Untreated total cholesterol concentrations were 488 to 1277 mg/dL (12.7 to 33.2 mmol/L). Angiography detected significant lesions in 7 of 11 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 40 publications
4
61
0
1
Order By: Relevance
“…Because the clinical relevance of prolonged dyslipidemia is well documented by studies on genetic causes of dyslipidemia, 46,47 we included all lipid measurements available for each participant and calculated the observed proportions of participants with sustained dyslipidemia during the study period. This was defined, as in our previous reports, 6 48 The observed proportions of participants with sustained dyslipidemia were then assessed according to ART groups and genetic score, summarized into tertiles (supplemental Tables II through IV).…”
Section: Discussionmentioning
confidence: 99%
“…Because the clinical relevance of prolonged dyslipidemia is well documented by studies on genetic causes of dyslipidemia, 46,47 we included all lipid measurements available for each participant and calculated the observed proportions of participants with sustained dyslipidemia during the study period. This was defined, as in our previous reports, 6 48 The observed proportions of participants with sustained dyslipidemia were then assessed according to ART groups and genetic score, summarized into tertiles (supplemental Tables II through IV).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis develops initially in the aortic root, causing supravalvular aortic stenosis, and then extends into the coronary ostia. The severity of atherosclerosis is proportional to the extent and duration of elevated plasma LDL-C levels (calculated as the cholesterol-year score) (4). If the LDL-C level is not effectively reduced, FH homozygotes die prematurely of atherosclerotic cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial wall calcification is common in patients with familial hypercholesterolemia, a genetic disorder of cholesterol metabolism. [3][4][5] Several studies have identified the relationship between the serum level of low-density lipoprotein cholesterol (LDL-C) and arterial wall calcification; moreover, lipid-lowering therapy using 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitors has been reported to inhibit the progression of arterial wall calcification. 6,7 In patients receiving long-term hemodialysis, elevated serum triglyceride (TG) levels and reduced high-density lipoprotein cholesterol (HDL-C) levels are risk factors for coronary artery calcification.…”
mentioning
confidence: 99%
“…Most of the previous studies used the "calcium score" determined by CT as a semiquantitative index of calcification of the aorta or coronary arteries. [3][4][5][6][7] However, the calcium score may not accurately reflect subtle changes in calcium deposit levels. To accurately quantify the degree of calcium deposition, we developed an image color analysis software program that can automatically determine the percentages of calcified volume against whole vascular volume (%ACV) using plain CT. 9 We previously reported a strong correlation between %ACV and aortic calcification dimension in aortas of autopsy specimens, the latter of which was determined using soft X-ray photographs.…”
mentioning
confidence: 99%